Neutrophil CD64 expression levels in IGRA-positive individuals distinguish latent tuberculosis from active disease - Raquel da Silva Corrêa; Luciana Silva Rodrigues; Leticia Hagge Lima Pereira; Otto Castro Nogueira; Janaína Leung; Marcela da S Sousa; Mariana de Andrea Hacker; Helio Ribeiro de Siqueira; Domênico Capone; Rogério Lopes Rufino Alves; Maria Cristina Vidal Pessolani; Veronica Schmitz; et al. (Memorias do Instituto Oswaldo Cruz, 2019)
BACKGROUND CD64 (FcγR1) is a high-affinity receptor for monomeric IgG1 and IgG3. Circulating neutrophils express very low amounts of CD64 on their surface. OBJECTIVES Our primary aim was to investigate the utility of neutrophil CD64 surface expression as a biomarker of active pulmonary tuberculosis (TB). We hypothesised that elevated neutrophil CD64 expression in TB infection would be associated with interferon gamma (IFN-g) as an inducer of CD64 expression. METHODS The expression level of CD64 per neutrophil (PMN CD64 index) was quantitatively measured with flow cytometry using a Leuko64 kit in samples from patients with TB and latent TB infection (LTBI) as well as healthy controls, as part of a prospective cohort study in Brazil. FINDINGS The PMN CD64 index in patients with TB was higher than that in healthy controls and LTBI. Receiver operating characteristic curve analyses determined that the PMN CD64 index could discriminate patients with TB from those with LTBI and healthy individuals. PMN CD64 index levels returned to baseline levels after treatment. CONCLUSIONS The positive regulation of CD64 expression in circulating neutrophils of patients with active TB could represent an additional biomarker for diagnosis of active TB and could be used for monitoring individuals with LTBI before progression of TB disease.